Electronic circular dichroism and nuclear magnetic resonance studies of peptides derived from the FKBP52‐interacting β‐turn of the hERα ligand‐binding domain. Issue 4 (25th January 2019) - Byrne, Cillian; Belnou, Mathilde; Baulieu, Etienne‐Emile; Lequin, Olivier; Jacquot, Yves
Abstract: When located at the surface of proteins, turns containing a Pro‐Gly (PG) motif are often involved in protein/protein interactions and may participate in intracellular signaling cascades. As such, conformationally constrained short protein‐derived turn peptides offer promising perspectives for the development of drug candidates in the context of interfering with protein/protein interactions. From X‐ray crystal structures of the human estrogen receptor α ligand‐binding domain (hERα‐LBD), we have identified a short peptide motif (residues 363‐367, sequence: RVPGF) that adopts a type II β‐turn and which is a substrate of the FK1 peptidyl‐prolyl cis ‐ trans isomerase (PPIase or rotamase) catalytic site of the immunophilin FKBP52, when synthesized independently from the protein. Using ECD and NMR spectroscopy in combination with molecular dynamics simulations, we have embarked on a conformational study of peptides derived from this sequence, and we have explored the effects resulting from N‐ and C‐termini chemical modifications, cyclization, as well as from the replacement of both the proline and its preceding residue by various natural and non‐natural amino acids. All peptides are found to explore several conformational states in aqueous solution, differing by the conformation of the peptide bond preceding the proline residue of the central VPG segment. Trans isomers are characterized by a conformational equilibrium between a type II β‐turn around PG and an extended conformation, while cis isomers adopt a type VIb β‐turn centered on the Xaa‐Pro segment. We show here how limited chemical modifications can deeply influence the turn conformation of this FKBP52‐interacting peptide. Abstract :